An introduction to the interleukin-1 family of cytokines - Sims, John (Henry Stewart Talks, 2011)
Introduction to IL-1 and its biology, Molecular characterization of IL-1 and its receptor, IL-1 secretion, signaling and regulation, IL-1 disease association, Other members of the IL-1 family, including structure, expression, receptors, regulation, IL-18, IL-33 and asthma, IL-36 and psoriasis